CARRYING CAPACITY AND CRACKING RESISTANCE AT THE SUPPORT ZONE OF HALVING JOINTS IN REIFORCED CONCRETE BEAMS - Chung, H. W.; Mpinzire, S. R. (Tanzania Journal of Engineering and Technology, 2018)
Abstract